Beyond the Usual Route: A Case of Postpartum Gonococcaemia in the Absence of Genital Symptoms - Norashikin, Samsudin; Nurnabilah, Zainuddin; Nurhafizah, Hatta; Alisa Hanum, Arba’eni @ Arbaen; Shasheila, Mohd Daud; Sue Marie Cheng, Kian Pei; Arlizan Baizura, Ariffin; Madzlifah, Ahadon (2025)
Neisseria gonorrhoeae is a Gram-negative diplococci associated with sexually transmitted infections (STIs), that typically infects the urethral, endocervical, rectal and pharyngeal mucosa1 . In women, gonococcal infections are often asymptomatic2 , which predisposes them to a higher risk of developing disseminated gonococcal infection (DGI). Here, we report a case of postpartum N.gonorrhoeae bacteraemia, also known as gonococcaemia.